2014
DOI: 10.1002/anie.201404029
|View full text |Cite
|
Sign up to set email alerts
|

Formal (4+1) Cycloaddition of Methylenecyclopropanes with 7‐Aryl‐1,3,5‐cycloheptatrienes by Triple Gold(I) Catalysis

Abstract: 7-Aryl-1,3,5-cycloheptatrienes react intermolecularly with methylenecyclopropanes in a triple gold(I)-catalyzed reaction to form cyclopentenes. The same formal (4+1) cycloaddition occurs with cyclobutenes. Other precursors of gold(I) carbenes can also be used as the C1 component of the cycloaddition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 63 publications
(19 reference statements)
0
55
0
2
Order By: Relevance
“…In 2014, we reported that 7‐aryl‐1,3,5‐cycloheptatrienes and methylenecyclopropanes react under gold(I) catalysis to give arylcyclopentenes (Table ) …”
Section: Higher Cycloadditions Of Gold(i) Carbenes Via Retro‐buchner mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, we reported that 7‐aryl‐1,3,5‐cycloheptatrienes and methylenecyclopropanes react under gold(I) catalysis to give arylcyclopentenes (Table ) …”
Section: Higher Cycloadditions Of Gold(i) Carbenes Via Retro‐buchner mentioning
confidence: 99%
“…A range of aryl groups can be efficiently transferred in the carbene fragment using down to only 1 mol % of [(JohnPhos)Au(MeCN)]SbF 6 in up to 0.5 g scale. Not only aryl methylenecyclopropanes can be employed, but also alkyl methylenecyclopropanes were tolerated, although in these cases, mixtures of regioisomers ranging from 1.5 : 1 to 10 : 1 were obtained …”
Section: Higher Cycloadditions Of Gold(i) Carbenes Via Retro‐buchner mentioning
confidence: 99%
“…Complications like the undesired consumption of 1 and 2 by a non‐selective homo‐reaction/oligomerization as noted in many related hydride systems, and/or fast isomerization were suppressed. And it avoids issues like competitive MCP‐opening by [2+2] or [3+3] dimerization, or insertion of MCP into Ni 0 , and rearrangements into cyclobutene when using Au I , all of which are related to other fascinating MCP reactivities . Notably, control experiments showed that the facile formation of 3 was not a result of NHC accelerated Ni 0 oxidative addition of 1 , and this observation is distinctly different from the in reactivity assumed for using NHC in place of P. Our results suggest an efficient rearrangement of 1 catalyzed by NHC/Ni II , thus achieving unparalleled reactivity, new scope, high selectivity, and efficiency.…”
Section: Methodsmentioning
confidence: 66%
“…Several processes were demonstrated for the carbene complexes alkylidenecyclopropanes (e.g. 1430) [1265]. Key steps in the proposed mechanism employing cyclobutenes are cyclopropanation followed by ring opening of the bicyclo[2.1.0]pentane system (e.g.…”
Section: Scheme 112mentioning
confidence: 99%